Triple Play Services- Based on New OCDMA Codes Utilizing FPGA Platform - Syed Alwee Aljunid, Syed Junid, Assoc. Prof. Dr.; Anuar, Mat Safar, Ir.; Hilal Adnan, Fadhil; Mohammad Nazri, Md. Noor (Malaysian Invention and Design Society (MINDS), 2010)
21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.